THE APPLICATION OF DEEP BREATHING RELAXATION THERAPY USING A FAN TO REDUCE PAIN IN SCHOOL-AGED CHILDREN DUE TO INVASIVE INTRAVENOUS INJECTION PROCEDURES IN THE EAST ASTER WARD OF SARDJITO HOSPITAL, YOGYAKARTA - Shelinna Suhaima Putri Nurul Wahidah; Sumarti Endah Purnamaningsih Maria Margaretha (Jurnal Kesehatan Karya Husada, 2025)
Background : School-age children often experience anxiety and pain from invasive procedures such as injections. Poorly managed pain can cause physical and emotional trauma. Deep breathing relaxation combined with playful techniques like blowing a pinwheel has been shown to divert attention and reduce perceived pain. Objective : To determine the effectiveness of deep breathing relaxation therapy with pinwheel blowing in reducing pain caused by intravenous injection in school-age children. Method : A descriptive case study involving a 12-year-old child experiencing pain from intravenous injection. The intervention was applied twice daily over 3 days. Pain was assessed using the Wong-Baker Faces Pain Scale. Data were collected through observation, interviews, and documentation. Results : The patient's pain scale decreased from an initial score of 8 (very painful) to 0 (no pain) after five therapy sessions. The child showed signs of relaxation and did not cry or resist the procedure by the final day. Conclusion : Deep breathing relaxation therapy with pinwheel blowing is effective in reducing pain from intravenous injection in school-age children. It can serve as a simple, non- pharmacological alternative that is both effective and child-friendly.